Strategi Guru dalam Meningkatkan Kualitas Pembelajaran Fikih di Madrasah Aliyah Negeri 1 Kota Bogor - Muhammad Farhan Farizi; Andri Ardiansyah; Amran Amran (Lembaga Yasin AlSys, 2025)
This study is motivated by the low quality of fiqh instruction in several madrasahs, which affects students’ comprehension and active participation in the learning process. Yet, fiqh as a subject plays a strategic role in shaping students’ religious character, understanding of Islamic law, and social behavior. The aim of this research is to identify the strategies used by teachers to improve the quality of fiqh instruction at Madrasah Aliyah Negeri (MAN) 1 Kota Bogor. A qualitative approach was employed, with data collected through interviews, observation, and documentation involving fiqh teachers of grades XI and XII. The findings reveal that teachers implement varied instructional strategies, such as Contextual Teaching and Learning (CTL), which links lesson content with students’ real-life experiences, and Problem Based Learning (PBL), which stimulates critical thinking and collaboration. Additionally, the use of digital, visual, and environmental-based learning media has proven effective in enhancing conceptual understanding and student engagement in class. The main conclusion of this study is that contextual, interactive, and innovative teaching strategies can holistically improve the quality of fiqh instruction across cognitive, affective, and psychomotor domains. The implications of this research underscore the importance of continuous professional development for teachers and institutional support to ensure the consistent implementation of innovative instructional strategies, thereby enhancing the overall quality of Islamic education in madrasah.